Internet, freedom and society: an analytical perspective (Polis (Santiago), 2018)
From viewing Internet as a cultural creation that reflects the principles and values of its inventors, the author examines how Internet and freedom became synonymous for many people around the world, an how after this states and churches reacted by trying to restore administrative control over expression and communication. He then raises the question of whether Internet is controllable, contrasting control and surveillance technologies with freedom technologies. Thus involving actors and principles: hackers and crackers, freedom and security ¸ the encryption of the message. The author exemplifies with the Spanish experience of Internet regulation.
Keywords: Internet; hackers; crackers; communication; freedom